Chemical Constituents of Garcinia Mangostana, G. Parvifolla, G. Griffitti and G. Diversifolia (Guttiferae) and Their Biological Activities - Tay, Bonnie Yen Ping (1996)
Four plants from the Garcinia genus were subjected to chemotaxonomic investigations with the isolation of a number of compounds. The structures of the compounds were established by spectroscopic methods such as MS, UV, IR, 1HNMR and 13C-NMR and by comparison with previous studies. The investigations of the pericarp of local grown Garcinia mangostana afforded known compounds which are mangostin, l3-mangostin, y-mangostin and gartanin.In investigations of the bark and heartwood of G. parvifolia collected from Ayer Hitam Forest Reserve, Puchong two xanthones, GP2, GH2 and stigmasterol were isolated. From another separate collection of the same species from Johor, three compounds were isolated: stigmasterol, an unidentified compound and an novel compound, GK3. Study on the leaves and stems of G. griffitti collected from Taman Negara , Pahang afforded two known compounds friedelin and (3-amyrin. Investigations on leaves and stems of G. diversifolia collected from Fraser's Hill also yielded friede!in. The plant extracts were evaluated for their biological activities against selected fungal and bacterial pathogens. The antifungal activity was performed using the 'Poison Food' method. The extracts from the test plant showed different antifungal activity towards the vegetative growth of plant pathogenic fungi ; Helminthosporium oryzae, Alternaria padwickii, Colletotrichum capsici, Fusarium oxysporum, Curvularia lunata and Pesta/otia theae The chloroform extract of the heartwood of G. parvifolia collected from Ayer Hitam Forest Reserve, Puchong was the most effective in inhibiting the mycelial growth for the test fungi. The antibacterial activity was tested using the 'Agar Diffusion' method. The extracts from the test plant also showed different antibacterial activity against the growth of six test bacteria ; Bacillus subtilis, E. coli, Erwinia carotovora, Microccoccus sp, Proteus vulgariS and Pseudomonas solanacearum. Chloroform extract of G. mangostana gave the highest average zone of inhibition, indicating the degree of its sensitivity.